Ibuprofen 400 mg is effective in women, and women are well represented in trials - Barden, J; Edwards, J; Moore, R; McQuay, H (BioMed Central, 2002)
Background: A recent article in the New Scientist argued that women were under-represented in clinical trials which, until now, had masked the finding that ibuprofen 400 mg was ineffective in women. Methods: Meta-analysis of randomised, double-blind placebo-controlled trials of ibuprofen 400 mg in acute pain, and use of individual patient information were planned to test the hypothesis that ibuprofen is ineffective in women. For each trial the proportion of women participating, the number of patients with at least 50% pain relief and the overall event rate for ibuprofen 400 mg and placebo was calculated. For each patient percentage pain relief was calculated, and the numbers of women and men achieving at least 50% pain relief used to calculate number-needed-to-treat (NNT) for ibuprofen 400 mg compared to placebo. Results: Thirty-seven included trials had 3,577 patients, 67% of whom were women. The proportion with at least 50% pain relief was unaffected by how many women were included. In an analysis of 678 individual patients the proportion of women and men with at least 50% pain relief was the same, NNT 3.4 (2.6 to 4.6) and 2.5 (2.0 to 3.3) respectively. Conclusion: There is no clinically meaningful difference in the efficacy of ibuprofen 400 mg between men and women experiencing moderate to severe postoperative pain and women were well represented.